Oxcarbazepine Induced Rhabdomyolysis and Acute Kidney Injury: A Case Report - Sara Yavuz Ileri; Nuray Can Usta (Case Reports in Nephrology)
The cause of acute skeletal muscle damage, defined as rhabdomyolysis, is multifactorial. Medicines are prominent among the most important reasons. The clinical significance of rhabdomyolysis lies in the fact that it can cause acute kidney injury (AKI) in 10%–40% of patients. In this presented case, oxcarbazepine, which is a preferred drug in the treatment of epilepsy and also in neuropathic pain in clinical practice, triggered rhabdomyolysis and subsequently caused the development of AKI. Through this case report, we aimed to emphasize that some serious side effects should not be forgotten when prescribing drugs in clinical practice.